Especies de Scarabaeoidea (Coleoptera) del CICOLMA, Veracruz, México - Rivera-Gasperín, Sara Lariza; Escobar-Hernández, Fernando (Instituto de Ecología, A.C., 2020)
Research in biodiversity and conservation in Mexico has advanced largely because they are linked to the existence of biological stations, biosphere reserves or protected natural areas. The Centro de Investigaciones Costeras La Mancha (CICOLMA) is one of the country's pioneer stations in coastal ecosystem research, however, studies on the beetle-fauna in this area have been minimal. The objective of this study was to document the fauna of Scarabaeoidea present in CICOLMA during April 2003 to March 2004, collections of beetles were made with direct and indirect techniques. A sample of 865 individuals of Coleoptera, Scarabaeoidea was obtained, of the families Cetoniidae, Melolonthidae, Passalidae, Scarabaeidae and Trogidae, representing 66 species of 41 genera. The species Cotinis pauperula Burmeister, 1847, Euetheola bidentata (Burmeister, 1847), Paranomala flavilla (Bates, 1888) and Pelidnota virescens Burmeister, 1844, represent new records for the state of Veracruz. A dichotomous key and data on the phenology are included.